THE CREATIVE HERITAGE OF MODEST LEVYTSKYI: THE RESEARCH POTENTIAL OF AN AUTHORIAL CORPUS OF HIS TEXTS - Lutsak, Svitlana; Yurchak, Halyna (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2026)
The article examines the life path and creative heritage of Modest Levytskyi from a corpus-linguistic perspective and substantiates the feasibility of creating an authorial text corpus of his works as a specialized electronic resource for comprehensive linguistic analysis. The study shows that that the multifaceted activity of the writer, physician, translator, educator, linguist, and public figure determined the genre, style, themes, and lexical-semantic diversity of his texts. It is shown that Modest Levytskyi’s creative legacy includes prose fiction, journalism, memoirs, translations, linguistic and medical works, which represent valuable material for studying the author’s idiolect, the dynamics of the Ukrainian literary language of the late nineteenth and early twentieth century, the formation of medical terminology, and the functioning of archaic, dialectal, socio-political, and professional vocabulary. The study emphasizes that Levytskyi’s texts have considerable potential for frequency, concordance, collocational, discourse, and sociolinguistic analyses. Particular attention is given to the textual peculiarities of the writer’s heritage, especially orthographic and punctuation variability, editorial differences, and the need for a unified metadata scheme for the texts. It is determined that corpus-based analysis of Modest Levytskyi’s works opens prospects for a comprehensive reconstruction of his linguistic worldview, identification of patterns of the author’s linguistic creativity, and deeper study of the history of the Ukrainian language. Despite the existence of several studies devoted to the life, works, and linguistic-stylistic features of Modest Levytskyi’s texts, his heritage has not yet been the subject of a comprehensive corpus-linguistic analysis. A systematic authorial corpus of the writer’s works has not yet been created, which determines the scientific novelty and relevance of this research.